Biocides: Durable Antibacterial Cotton Fabrics Based on Natural Borneol‐Derived Anti‐MRSA Agents (Adv. Healthcare Mater. 11/2020). Issue 11 (10th June 2020) - Yang, Liu; Zhan, Chengdong; Huang, Xiangyue; Hong, Liangzhi; Fang, Liming; Wang, Wen; Su, Jianyu
Abstract : In article number 202000186 by Liangzhi Hong, Jianyu Su and coworkers, a water‐soluble antibacterial agent is developed by integrating membrane‐active natural borneol with a hydrophilic PDMAEMA chain. Cotton fabrics with sustained antibacterial activity can be fabricated by grafting the borneol‐based antibacterial agents on the surface.